Perkiraan dampak ACFTA terhadap kesempatan kerja pada industri tekstil dan produk dari tekstil di Indonesia - Rajagukguk, Zantermans (Jurnal Kependudukan Indonesia, 2013)
ASEAN-China Free Trade Agreement (ACFTA) does not only serve as talking point but also works as an interesting study. Some circles see it as a step forward that will provide a positive impact for the employment, however, there are others who think otherwise, especially when it comes to its impact on the textile industry and products (TPT). This paper is a summary of the research that was conducted by the author as a researcher for the Center for Employment Research, the Ministry of Manpower and Transmigration. The analytical approach that will be taken in estimating the impact of ACFTA is the Dynamic Social Accounting Matrix (DySAM) Analysis (analyzing the trade-output-employment), an approach that currently receives a lot of attention. From the results of the simulation using the DySAM approach, it shows that without any real support in the form of incentive policies to mitigate the impact of ACFTA, the reduction in import duties (tariff) as a consequence of the implementation of ACFTA will give a negative impact on the output as well as the employment in the textile industry. The simulation results show that the greater the fall in import duties, the more the reduction in the output and the employment. Based on the above conclusions, the government and all the stakeholders need to take various measures, in both the prevention as well as the mitigation of the impact of the implementation of the ACFTA.